HP Laser Jet Internet and Business Productivity Software (Powerful Internet and Productivity Software Included) - Hewlett Packard (Hewlett Packard, 1998)
Program dan File dalam bentuk Rtf, Gambar, dll; Isi: ByDesign, IE40, LabelPro, Printer, Seeker, Wacker, Xtras, dll; Judul dalam kemasan.